Dermoscopic, Histological, Confocal Microscopy Correlation of Atypical-Dysplastic Melanocytic Nevi - Cantisani, Carmen; Ambrosio, Luca; Annessi, Emanuele; Longo, Caterina; Farnetani, Francesca; Pezzini, Claudia; Condorelli, Alessandra; Annessi, Giorgio; Reggiani Bonetti, Luca; Guida, Stefania; Cota, Carlo; Tammaro, Antonella; et al. (Dermatology Practical & Conceptual, 2024)
Introduction: The term "atypical melanocytic nevus" (AMN) is used as a synonym for dysplastic nevus (DN) in clinical practice. Although the criteria for diagnosis of AMN/DN by the Agency for Research on Cancer helps to differentiate AMN/DN from common acquired nevi, they do not have high degrees of specificity, as they are similar to those used for the diagnosis of melanoma.Objectives: In this retrospective study we evaluated the correlation and diagnostic concordance of dermoscopy, confocal microscopy, and histological examination in 50 AMN.Methods: A graded scale was used to compare histological examination with dermoscopy and confocal microscopy. Low magnification histological images of only the central part of lesions were examined. This allowed histological diagnoses based almost exclusively on architectural criteria instead of simultaneously architectural and cytological, as in the global histological examination.Results: Our data demonstrate that the diagnostic accuracy of dermoscopy and confocal microscopy diagnosis of the clinical aspects of AMN/DN as nevi or melanomas tends to be equivalent, being fair for nevi and excellent for melanomas. The total percentage of AMN suggested that the accuracy of confocal microscopy in the diagnosis of melanoma (86.7%) is greater than that of dermoscopy (73.3%).Conclusions: This study demonstrated that diagnostic assessments of AMN/DN by dermoscopy and confocal microscopy are accurate and often coincide with those of histological examination and that their combined use helps to better manage and monitor these patients by facilitating early detection of melanomas and reducing unnecessary excisions of benign melanocytic lesions.